The advanced e-Learning technologies at the university - Kuchuk, N. G. (ISMA University of Applied Science, 2021)
The analysis of many existing e-Learning methods and the prospects for further research in this area show the need to influence the development of education in a special way. The purpose of this research is studing the advanced methods of e-Learning. Their analysis and development of information and communication educational technologies, identification of new trends in the development of e-learning.
Keywords: E-Learning; university; education; educational technologies; students